Efficiency of intraoperative frozen section analysis of central neck lymph node dissection in patients with papillary thyroid carcinoma. Issue 5 (June 2018) - Kim, Mi Jin; Kim, Cheol Seung; Kim, Je Roung; Park, Young Sam
Abstract : Background and Objective: Because of the high survival rate and low recurrence rate of thyroid carcinoma, the therapeutic process is changing from aggressive treatment to submissive treatment. Currently, choosing central node dissection (CND) as a treatment option is considered controversial since. This approach has been shown to have poor outcomes. Therefore, we conducted this study to confirm whether the intraoperative frozen section analysis (IFSA) of CND during surgery affects treatment outcomes of patients with this type of cancer. Materials and Methods: First, we collected the medical records of 265 patients who underwent surgery for papillary thyroid cancer at the Presbyterian Medical Center from 2014 to 2016. The patients were divided into 2 groups: IFSA and non-IFSA. The outcomes of treatment options were then assessed. We analyzed the sensitivity, specificity, positive predictive value, negative predictive value, and accuracy of IFSA of CND. Results: Of the 265 patients in the study, 74 patients (89%) in the IFSA group and 95 patients (52.2%) in the non-IFSA group were treated appropriately ( P -value=0.000). The sensitivity, specificity, positive predictive value, negative predictive value, and accuracy of IFSA of CND were 93.5%, 100%, 100%, 96.3%, and 97.5%, respectively. Conclusions: The IFSA of CND is a useful method to confirm central node metastasis during surgery. Determining the range of surgery required for each patient using this method is useful for ensuring minimal complications and for providing a successful, effective oncologic surgery.